Role of training programs approved by the Iraqi Athletics Federation on the performance of Iraqi coaches - Sajad Mohammad Ebadi Alkhafaji; Zahrasadat Mirzazadeh; Mahdi Talebpour; Mohammad Keshtidar; Mohamed Abadi Abed (Universidad de Murcia, 2022)
Article accepted. The article will be published here soon. Pending final quality checks.